A ideia de justiça - ou o princípio de racionalidade - nos crimes contra a ordem tributária - Mariane Andreia Cardoso dos Santos (2019)
This study is about the analysis of crimes against the tax order from a perspective basedon the principle of rationality of law - or the idea of justice. The first part seeks toelucidate the elements that perpass the existence of the legal duty, namely coercivity,that is, the possibility of using the state apparatus in an institutionalized way, as aconsequence of violation of the duty set forth in the norm, whose addressee is thesubject that should suffer the sanction. Coercion is inherent in the juridical order,although only as a possibility, even though it is not a basis for the validity of legal duty,proving to be essential to the juridical phenomenon because it is an instrument for therealization of the law and, therefore, condition of its existence. In the dialectic of thenegation of law, the element that makes the law reconcile with itself is the sanction;specifically in crime, the penalty. Based on these considerations, the aspects of the taxstandard that guide the application of the parameters set forth in the CTN for taxliability are analyzed. This is the background of the evaluation of the elements thatpervade the characterization of the criminal unfair can be analyzed under the objectiveprisms, relative to the set of material characters predicted in the type, and subjective,which concerns the psychic aspects of the crime related to the active subject of crime,which, in the case of crimes against the tax order, must be specifically aimed at provingthe fraud. Only in compliance with the legal requirements of tax liability can criminalprosecution be considered, which can not be merely a collection instrument in order toforce the individuals to collect amounts corresponding to non-existent tax debts.